Rubber diaphragm for all-vanadium redox flow battery and preparation method of rubber diaphragm

By optimizing the formulation of the rubber diaphragm, using raw materials without oil softeners, and adding specific reinforcement and additives, the problem of insufficient corrosion resistance of ethylene propylene rubber in all-vanadium liquid flow battery electrolyte is solved, achieving higher corrosion resistance and lower production costs.

CN119735899AInactive Publication Date: 2025-04-01NINGBO DUNHONG SEALING TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510247663.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing ethylene propylene ternary rubber has poor corrosion resistance in all vanadium flow battery electrolytes, making it difficult to meet the needs of large-scale applications.

Method used

By optimizing the formulation of the rubber diaphragm, using raw materials without oil softeners, adding carbon black N990 and barium sulfate as reinforcement, and cross-linking using a peroxy vulcanization system, combining anti-aging agent TMQ and antioxidant 1010 to improve the corrosion resistance of the rubber.

Benefits of technology

The corrosion resistance of rubber diaphragms in all vanadium liquid flow battery electrolyte is significantly improved, the risk of oil precipitation is reduced, the problems of electrolyte contamination and unstable performance are avoided, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a rubber diaphragm for an all-vanadium redox flow battery and a preparation method of the rubber diaphragm, and the rubber diaphragm comprises a raw material without an oil softener; the rubber diaphragm is prepared from the following raw materials in parts by mass: 95 to 100 parts of ethylene propylene diene monomer, 95 to 100 parts of an N990 reinforcing agent, 10 to 15 parts of a BaSO4 reinforcing agent, 1 to 1.2 parts of an anti-aging agent, 0.4 to 0.7 part of an antioxidant, 0.5 to 0.6 part of a cross-linking agent, 1 to 1.5 parts of a dispersing agent, 1 to 1.5 parts of an active agent and 4 to 7 parts of a vulcanizing agent. And the corrosion resistance of the ethylene propylene diene monomer in the electrolyte of the all-vanadium redox flow battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rubber diaphragm, and more particularly to a rubber diaphragm for an all-vanadium liquid flow battery and a preparation method thereof. Background Art

[0002] The all-vanadium flow battery stack in the energy storage industry is relatively large in size and requires a large amount of rubber diaphragms. The commonly used rubber material is EPDM. The electrolyte of the all-vanadium flow battery is a strong acidic substance, which is quite corrosive to rubber. The advantages of EPDM are low price and good low temperature resistance, but its corrosion resistance in the electrolyte of the all-vanadium flow battery is slightly poor. Summary of the invention

[0003] The first object of the present invention is to provide a rubber diaphragm for an all-vanadium redox flow battery, which improves the corrosion resistance of EPDM rubber in the electrolyte of the all-vanadium redox flow battery.

[0004] The above technical objectives of the present invention are achieved through the following technical solutions: A rubber diaphragm for an all-vanadium liquid flow battery comprises raw materials that do not contain an oil softener; the raw materials comprise, by weight, 95-100 parts of EPDM rubber, 95-100 parts of N990 reinforcing agent, 10-15 parts of BaSO4 reinforcing agent, 1-1.2 parts of an antioxidant, 0.4-0.7 parts of an antioxidant, 0.5-0.6 parts of a cross-linking agent, 1-1.5 parts of a dispersant, 1-1.5 parts of an activator and 4-7 parts of a vulcanizing agent.

[0005] Preferably, the antioxidant is 1.1 parts, and the antioxidant is TMQ.

[0006] Preferably, the antioxidant is 0.45 parts and the antioxidant is 1010.

[0007] Preferably, the cross-linking agent is 0.57 parts, and the cross-linking agent is TMPTMA.

[0008] Preferably, the dispersant is 1 part, and the dispersant is polyethylene wax.

[0009] Preferably, the active agent is 1 part, and the active agent is stearic acid.

[0010] Preferably, the vulcanizing agent is 6 parts, and the vulcanizing agent is DCP 40%.

[0011] Preferably, 100 parts of EPDM rubber, 96 parts of N990 reinforcing agent, and 11 parts of BaSO4 reinforcing agent.

[0012] The second object of the present invention is to provide a method for preparing a rubber diaphragm for an all-vanadium redox flow battery, and to prepare EPDM rubber with improved corrosion resistance.

[0013] The above technical objectives of the present invention are achieved through the following technical solutions: A method for preparing a rubber diaphragm for an all-vanadium liquid flow battery comprises the following steps: Step 1: Plastication: put the EPDM rubber into an internal mixer for plastication at a temperature of 50-70°C for about 5-10 minutes to soften the rubber; Step 2: Add reinforcing agent, add N990 reinforcing agent and BaSO4 reinforcing agent in turn, continue mixing, control the temperature at 70-90℃, and mix for about 10-15 minutes to ensure that the reinforcing agent is evenly dispersed; Step 3: Add additives, antioxidants, crosslinking agents, dispersants and activators, continue mixing, control the temperature at 80-100°C, and mix for about 5-10 minutes to ensure that the additives are evenly dispersed; Step 4: Add the vulcanizing agent, finally add the vulcanizing agent, continue mixing, control the temperature at 90-110℃, and the time is about 5-10 minutes to ensure that the vulcanizing agent is evenly dispersed; Step 5: Sheeting: Take the mixed rubber material out of the internal mixer and put it into the open mixer for sheeting. The temperature is controlled at 50-70°C for about 5-10 minutes to make the rubber material sheeting evenly. Step 6: Vulcanization: vulcanization is carried out in a flat vulcanizer or injection molding machine, the temperature is controlled at 150-170°C, the pressure is controlled at 10-15MPa, and the time is about 10-20 minutes. The specific time is adjusted according to the type and amount of vulcanizing agent; Step 7: Post-processing: the vulcanized rubber product is taken out of the mold, cooled naturally to room temperature, and the rubber product is trimmed to remove burrs and flash.

[0014] Preferably, in step 6, preforming is first performed by placing the rubber material into a mold and pressing it into a rubber blank. The preforming temperature is 80° C.-100° C. and the time is about 5-10 minutes.

[0015] In summary, the present invention has at least one of the following beneficial effects: (1) Carbon black N990 and barium sulfate are used as reinforcing agents, and no oil softener is added to the raw material formula. Although the addition of oil softeners can improve the processability of the rubber, there is a risk of oil precipitation, which will contaminate the electrolyte and affect the performance stability of the product. Because in an acidic environment, the rubber itself needs to have good chemical corrosion resistance. However, if the rubber has been penetrated or swollen by oil, acidic substances are more likely to invade the inside of the rubber and accelerate the corrosion process; the presence of oil may react with the acid to generate more corrosive substances, further aggravating the corrosion of the rubber; therefore, if no oil softener is added to the raw material, the precipitation of oil in the rubber can be greatly reduced, which greatly improves the corrosion resistance of the rubber in the electrolyte of the all-vanadium liquid flow battery.

[0016] N990 has large particle size and small relative area, and can be filled in large amounts in rubber. Large amounts of use will not significantly reduce the performance of the rubber. At the same time, the rubber using N990 has excellent processability and good performance stability. Even without using oil softeners, the rubber has good fluidity.

[0017] Barium sulfate has high thermal and chemical stability and good electrical insulation. Adding it to the rubber can improve the corrosion resistance and aging resistance of the rubber and increase its resistivity.

[0018] (2) The peroxide vulcanization system is used. The peroxide vulcanization system produces free radicals through the decomposition of peroxide, which triggers the cross-linking reaction between rubber molecules. The peroxide is DCP, and the cross-linking bond is mainly CC bond. It has good stability, heat resistance and corrosion resistance, making the product size stable and the size fluctuation range small.

[0019] (3) The protective system uses antioxidant TMQ and antioxidant 1010. The combined use of these two additives can effectively protect the rubber from aging, maintain the stability of rubber performance, make the product size stable, and reduce the size fluctuation, thereby extending the product life.

[0020] TMQ has a good effect on thermal oxidative aging and also has a relatively strong inhibitory effect on metal-catalyzed oxidation reactions (the electrolyte contains a variety of metal ions, which are common catalysts for oxidation reactions); the electrolyte has strong oxidizing properties, and the addition of antioxidant 1010 can improve the oxidation resistance of rubber.

[0021] (4) The EPDM rubber used in this design has the advantage of low cost. The same type of rubber with better corrosion resistance in acidic electrolyte is fluororubber. Due to the difficulty of manufacturing process and other factors, the price of fluororubber is higher than that of EPDM rubber. In this scheme, the EPDM rubber has improved its chemical corrosion resistance in acidic electrolyte, and its price is lower when used in all-vanadium liquid flow battery stacks. DETAILED DESCRIPTION

[0022] Example 1, a rubber diaphragm for an all-vanadium redox flow battery, comprising a raw material that does not contain an oil softener; the raw material comprises the following components by mass: 100 parts of EPDM rubber; N990 reinforcing agent 95 parts, N990 (carbon black N990) is a carbon black with low specific surface area. Although the reinforcing effect of N990 is not as good as that of carbon black with high specific surface area (such as N330, N550), it can still provide a certain mechanical strength for EPDM (ethylene propylene diene monomer rubber) and improve the tensile strength, tear strength and wear resistance of rubber; N990 has a larger particle size and a lower structure, which can reduce the viscosity of EPDM rubber, improve processing fluidity, and make mixing, calendering, extrusion and other processes easier to operate; BaSO4 reinforcing agent 11 parts; BaSO4 is an inert inorganic filler. Adding it to EPDM can increase the volume of the rubber and reduce production costs while maintaining the basic properties of the rubber; 1.1 parts of antioxidant, the antioxidant is TMQ, the chemical name of TMQ is 2,2,4-trimethyl-1,2-dihydroquinoline polymer, which is a commonly used rubber antioxidant. Its main function is to prevent rubber from aging due to thermal oxidation, thereby extending the service life of rubber materials; 0.45 parts of antioxidant, antioxidant is 1010, antioxidant 1010, chemical name is pentaerythritol ester, it is a white crystalline powder, odorless and tasteless, with a melting point of 110℃-125℃. Antioxidant 1010 mainly plays the role of delaying aging, maintaining mechanical properties, preventing discoloration, improving heat resistance and extending service life in EPDM rubber. It is an important additive in the processing and application of EPDM rubber.

[0023] 0.57 parts of crosslinking agent, the crosslinking agent is TMPTMA, which is a trifunctional monomer containing three methacrylate groups, and can react with rubber molecules under the action of free radicals to form a CC bond crosslinking network; 1 part of dispersant, the dispersant is polyethylene wax; 1 part of active agent, the active agent is stearic acid; 6 parts of vulcanizing agent, the vulcanizing agent is DCP 40%. DCP (dicumyl peroxide) is a commonly used organic peroxide, widely used as a rubber vulcanizing agent. DCP 40% refers to a mixture containing 40% dicumyl peroxide.

[0024] The following performance tests were performed on the rubber diaphragm for the all-vanadium liquid flow battery in this implementation: The performance test of rubber diaphragms for all-vanadium flow batteries was carried out in accordance with the Chinese national standard GB / T 531.1, entitled "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore durometer method (Shore hardness)". This standard specifies the method for determining the indentation hardness of vulcanized rubber or thermoplastic rubber using a Shore durometer. The test results are shown in Table 1.1; hardness, Shore A refers to the Shore A hardness test, and the unit of Shore A hardness is degree.

[0025] Table 1.1 Test items index Test value Hardness, Shore A 70±2 70

[0026] The performance test of rubber diaphragms for all-vanadium redox flow batteries was carried out according to the Chinese national standard GB / T 528, titled "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber". This standard specifies the test method for the stress-strain properties of vulcanized rubber or thermoplastic rubber under tension. The test results are shown in Table 1.2.

[0027] Table 1.2 Test items index Test value Tensile strength, MPa ≥9 12.4 Elongation, % ≥200 256

[0028] The performance test of rubber diaphragms for all-vanadium liquid flow batteries was carried out in accordance with the Chinese national standard GB / T 7759.1, entitled "Determination of compression set of vulcanized rubber or thermoplastic rubber Part 1: At room temperature, high temperature or low temperature conditions". This standard specifies the test method for the permanent deformation of vulcanized rubber or thermoplastic rubber under compression. The test results are shown in Table 1.3; compression set refers to compression set, and 100℃*22h refers to the test time of 22 hours at 100 degrees Celsius.

[0029] Table 1.3 Test items index Test value Pressure change, 100℃*22h ≤25 6

[0030] The performance test of rubber diaphragm for all-vanadium liquid flow battery was carried out according to the Chinese national standard GB / T 1682, entitled "Single Specimen Method for Determination of Low-Temperature Brittleness of Vulcanized Rubber". This standard specifies the test method for the brittleness of vulcanized rubber in low-temperature environment. The test results are shown in Table 1.4.

[0031] Table 1.4 Test items index Test value Low temperature brittleness -40 -50

[0032] The performance test of rubber diaphragms for all-vanadium redox flow batteries is carried out according to the Chinese national standard GB / T 1692, titled "Determination of insulation resistivity of vulcanized rubber". This standard specifies the test method for insulation resistivity of vulcanized rubber, and the test results are shown in Table 1.5; Ω·cm represents the unit, which means ohm centimeters.

[0033] Table 1.5 Test items index Test value Insulation resistivity, Ω·cm <![CDATA[≥1*10 8 ]]> <![CDATA[1*10 10 ]]>

[0034] The rubber diaphragm for all-vanadium liquid flow battery was tested for heat aging resistance at 100℃*70h. The test standard is the Chinese national standard GB / T 3512, titled "Hot Air Aging Test Method for Vulcanized Rubber or Thermoplastic Rubber". This standard specifies the method for aging performance testing of vulcanized rubber or thermoplastic rubber in a hot air environment. The test results are shown in Table 2; 100℃*70h means testing at 100 degrees Celsius for 70 hours.

[0035] Table 2 Test conditions Test items index Test value Heat aging resistance, 100℃*70h Hardness change, Shore A 0~+10 0 Heat aging resistance, 100℃*70h Strength change rate, % ≤20 -1.3 Heat aging resistance, 100℃*70h Elongation change rate, % ≤20 -3.6

[0036] The rubber diaphragm for all-vanadium liquid flow battery was used for the performance test of all-vanadium liquid flow battery electrolyte at 45℃*7d. The test standard is the Chinese national standard GB / T 1690, titled "Test method for liquid resistance of vulcanized rubber or thermoplastic rubber". This standard specifies the test method for the performance change of vulcanized rubber or thermoplastic rubber when it comes into contact with liquid media. The test results are shown in Table 3; 45℃*7d means testing at 45 degrees Celsius for 7 days.

[0037] Table 3 Test conditions Test items index Test value All-vanadium liquid flow battery electrolyte, 45℃*7d Hardness change, Shore A -5~+10 +1 All-vanadium liquid flow battery electrolyte, 45℃*7d Strength change rate, % ±15 +7.3 All-vanadium liquid flow battery electrolyte, 45℃*7d Elongation change rate, % ±15 +2.4 All-vanadium liquid flow battery electrolyte, 45℃*7d Volume change rate, % ±5 +0.30

[0038] The performance test of the rubber diaphragm for all-vanadium liquid flow battery was carried out in a 50% sulfuric acid solution at 45℃*7d. The test standard is the Chinese national standard GB / T 1690, entitled "Test method for liquid resistance of vulcanized rubber or thermoplastic rubber". This standard specifies the test method for the performance change of vulcanized rubber or thermoplastic rubber when it comes into contact with liquid media. The test results are shown in Table 4.

[0039] Table 4 Test conditions Test items index Test value 50% sulfuric acid solution, 45℃*7d Hardness change, Shore A -5~+10 +1 50% sulfuric acid solution, 45℃*7d Strength change rate, % ±15 +5.6 50% sulfuric acid solution, 45℃*7d Elongation change rate, % ±15 +4.1 50% sulfuric acid solution, 45℃*7d Volume change rate, % ±5 +0.28

[0040] Example 2, a method for preparing a rubber diaphragm for an all-vanadium redox flow battery in Example 1, wherein the rubber is prepared using the raw material formula in the example, and the specific steps are as follows: Step 1: Plastication: put the EPDM rubber into an internal mixer for plastication at a temperature of 50-70°C for about 5-10 minutes to soften the rubber; Step 2: Add reinforcing agent, add N990 reinforcing agent and BaSO4 reinforcing agent in turn, continue mixing, control the temperature at 70-90℃, and mix for about 10-15 minutes to ensure that the reinforcing agent is evenly dispersed; Step 3: Add additives, antioxidants, crosslinking agents, dispersants and activators, continue mixing, control the temperature at 80-100°C, and mix for about 5-10 minutes to ensure that the additives are evenly dispersed; Step 4: Add the vulcanizing agent, finally add the vulcanizing agent, continue mixing, control the temperature at 90-110℃, and the time is about 5-10 minutes to ensure that the vulcanizing agent is evenly dispersed; Step 5: Sheeting: Take the mixed rubber material out of the internal mixer and put it into the open mixer for sheeting. The temperature is controlled at 50-70°C for about 5-10 minutes to make the rubber material sheeting evenly. Step 6: Preforming. Preforming is to put the rubber into the mold and press it into a rubber blank. The preforming temperature is 80℃-100℃ and the time is about 5-10 minutes. During production, the rubber blank is put into the mold and vulcanized under high temperature and high pressure. The advantage of preforming is that the product size will be more uniform and stable, and the yield rate is high; Re-vulcanization: vulcanization is carried out in a flat vulcanizer or injection molding machine, with the temperature controlled at 170-180°C and the pressure controlled at 10-15MPa for about 10-20 minutes. The specific time is adjusted according to the type and amount of vulcanizing agent. Step 7: Post-processing: the vulcanized rubber product is taken out of the mold, cooled naturally to room temperature, and the rubber product is trimmed to remove burrs and flash.

[0041] The rubber diaphragm prepared in this scheme is used in the all-vanadium liquid flow battery stack, and the rubber diaphragm has strong corrosion resistance in the all-vanadium liquid flow battery electrolyte.

[0042] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A rubber diaphragm for an all-vanadium liquid flow battery, characterized in that: Includes raw materials that do not contain oil softeners; Calculated by mass, the raw materials include: 95-100 parts of EPDM rubber, 95-100 parts of N990 reinforcing agent, 10-15 parts of BaSO4 reinforcing agent, 1-1.2 parts of antioxidant, 0.4-0.7 parts of antioxidant, 0.5-0.6 parts of cross-linking agent, 1-1.5 parts of dispersant, 1-1.5 parts of activator and 4-7 parts of vulcanizer.

2. The rubber diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: 1.1 parts of antioxidant, the antioxidant is TMQ.

3. The rubber diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: Antioxidant 0.45 parts, antioxidant is 1010.

4. The rubber diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: 0.57 parts of cross-linking agent, which is TMPTMA.

5. The rubber diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: 1 part of dispersant, the dispersant is polyethylene wax.

6. The rubber diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: 1 part of active agent, the active agent is stearic acid.

7. The rubber diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: 6 parts of vulcanizing agent, the vulcanizing agent is DCP40%.

8. A rubber diaphragm for an all-vanadium redox flow battery according to any one of claims 1 to 7, characterized in that: 100 parts of EPDM rubber, 96 parts of N990 reinforcing agent, and 11 parts of BaSO4 reinforcing agent.

9. A method for preparing the rubber diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: The following steps are involved: Step 1: Plastication: put the EPDM rubber into an internal mixer for plastication at a temperature of 50-70°C for about 5-10 minutes to soften the rubber; Step 2: Add reinforcing agent, add N990 reinforcing agent and BaSO4 reinforcing agent in turn, continue mixing, control the temperature at 70-90℃, and mix for about 10-15 minutes to ensure that the reinforcing agent is evenly dispersed; Step 3: Add additives, antioxidants, crosslinking agents, dispersants and activators, continue mixing, control the temperature at 80-100°C, and mix for about 5-10 minutes to ensure that the additives are evenly dispersed; Step 4: Add the vulcanizing agent, finally add the vulcanizing agent, continue mixing, control the temperature at 90-110℃, and the time is about 5-10 minutes to ensure that the vulcanizing agent is evenly dispersed; Step 5: Sheeting: Take the mixed rubber material out of the internal mixer and put it into the open mixer for sheeting. The temperature is controlled at 50-70°C for about 5-10 minutes to make the rubber material sheeting evenly. Step 6: Vulcanization: vulcanization is carried out in a flat vulcanizer or injection molding machine, the temperature is controlled at 150-170°C, the pressure is controlled at 10-15MPa, and the time is about 10-20 minutes. The specific time is adjusted according to the type and amount of vulcanizing agent; Step 7: Post-processing: the vulcanized rubber product is taken out of the mold, cooled naturally to room temperature, and the rubber product is trimmed to remove burrs and flash.

10. A preparation method according to claim 9, characterized in that: In step 6, preforming is first performed by placing the rubber material into a mold and pressing it into a rubber embryo. The preforming temperature is 80°C-100°C and the time is about 5-10 minutes.

Citation Information

Patent Citations

  • Ethylene-propylene-diene monomer rubber for sealing flow battery and preparation method of ethylene-propylene-diene monomer rubber

    CN118307890A